Determinants of intention buying local foods: a conceptual framework - Artha, Bhenu; Tunjung Sari, Utami; Bahri; Permata Sari, Niken (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Consuming food from the area has grown in popularity. Local foods have positive effects on the environment, economy, society, and health. In particular, we investigate how consumer beliefs about locavorism is predicted by antecedent factors (i.e., values of collectivistic and individualistic). We also investigate how locavorism is predicted by consumer travel behavior and city branding. We also look at how these sets of beliefs affect consumer attitudes toward and intentions to buy local foods in Special Region of Yogyakarta. By addressing the antecedents of locavorism and placing the constructs of locavorism within an integrated network of antecedents and effects, this study closes a research gap in the field of local food research. We use 9-point scales for questionnaire, which is a novelty in this study, where previous studies used 7 scales. The 9-point scales are used to rate as closely as possible the respondent's response to what is described. This study's conclusions have ramifications for regional food marketers.